SWOT Analysis of the Independent Audit Profession in Iran - Mohammadreza Mehrabanpour (University of Tehran, 2021)
Objective: In the country's economic system, the independent audit profession has a key position and it has faced many challenges and changes in recent years. In order to maximize its value and prestige, the profession's stakeholders and participants need a strategic understanding of the internal and external factors that influence it. The purpose of this study is to provide a SWOT analysis of the independent audit profession in Iran. Methods: This research is a qualitative and grounded theory study. Data collection is done by a triangular approach including 20 semi-structured interviews, 38 secondary interviews, and qualitative analysis of 500 documents from the professional journals of Iran. Results: The results of the SWOT analysis indicate the severity of the expectations gap and the destructive effects of the situation of the country's economic enterprises and the political and economic conditions on Iran's independent auditing profession. The strengths and cornerstone of the Iranian independent audit profession are professional structures and infrastructures, established legal society for Iranian certified public accountants, development of accounting and auditing standards, and the professional associations. The profession's weaknesses are low audit fees, weak interaction with stakeholders, structural and legal problems, control quality of the CPAs' profession, and lack of solidarity and synergy. The profession's opportunities can be explained from four dimensions, including attracting stakeholders' attention and trust, development of international relations, enlargement of audit firms, and restructuring the pillars of the profession. The main threats of the profession are the stakeholders' expectations gap, conditions of the country's enterprises, and the political and economic conditions of Iran. Conclusion: According to the achieved results from this SWOT analysis, policymakers and stakeholders must do the strategic management of strengths and opportunities to resolve the growing factors that weaken and threaten the profession in the country.